The role of adrenal venous sampling and computed tomography in the management of primary aldosteronism. Issue 2 (February 2021) - Ma, Delin; Liu, Xiaming; Zeng, Liwen; Yuan, Penghui; Liu, Zheng; Xie, Junhui; Yuan, Gang; Wang, Shaogang; Yu, Xuefeng; Yang, Yan; Xu, Anhui
Abstract : Background: The role of adrenal venous sampling (AVS) has been challenged by some recent evidence. This study aimed to compare the role of AVS and computed tomography (CT) in the management of primary aldosteronism. Methods: Patients who underwent unilateral adrenalectomy for primary aldosteronism at a single center between January 2015 and December 2018 were included, and postoperative outcomes of the patients who underwent surgery based on CT ( n  = 195) or AVS ( n  = 40) were compared. The data of all the patients who underwent AVS successfully ( n  = 75) during this period were also collected and analyzed. Results: There were no significant differences between the CT-guided and AVS-guided adrenalectomies in most of the postoperative outcomes, and the proportion of patients achieving cure of hypokalemia (CT vs. AVS, 98.3 vs. 96.4%) and alleviation of hypertension (89.2 vs. 92.9%) were similar between the two groups. However, since the baseline characteristics of the two groups were not identical, the AVS-guided group showed greater improvement in postoperative hypokalemia and greater reduction in the number of antihypertensive medications than the CT-guided group. In addition, for the 75 patients who underwent AVS successfully, the concordance rate between CT abnormalities and AVS lateralization was 60.0% in total, and 22.7% patients changed treatment plans according to the AVS results. Conclusion: Although the clinical outcomes were not significantly different between the CT-guided and AVS-guided group, the AVS-guided group seemed to benefit more from the surgery, and a considerable number of patients with primary aldosteronism would have received inappropriate treatment if they did not undergo AVS.